Payer type does not impact patient-reported outcomes after primary total knee arthroplasty - Feng, James E. (Arthroplast Today, 2019)
BACKGROUND: There is a paucity of literature assessing whether payer type has an impact on postoperative patient-reported outcomes (PROs) after total knee arthroplasty (TKA). The aim of this study was to comparatively evaluate TKA PROs among patients with commercial and Medicare insurance. METHODS: We conducted a single-center, retrospective review of patients operated between January 2017 and March 2018. Knee Disability and Osteoarthritis Outcome Score Junior (KOOS-Jr) and Veterans RAND 12 Health Survey (VR-12) Physical Component (VR-12 PCS) and Mental Component (VR-12 MCS) PRO scores were collected prospectively at baseline and 12 weeks postoperatively via an electronic patient rehabilitation application. Univariable and multivariable linear regressions were utilized to assess the effects of patient insurance type on PRO. RESULTS: In total, 193 TKA candidates had commercial (n = 91) or Medicare (n = 102) as their primary payer type. Demographic variables including age, gender, body mass index, and race varied significantly between the cohorts (P < .05). Length of stay and discharge disposition also varied significantly (P < .05). When compared with commercial payers, Medicare beneficiaries demonstrated a 4.13 ± 2.06 increase in Knee Disability and Osteoarthritis Outcome Score JR. scores at baseline (P < .05). However, after adjusting for patient-specific demographic and perioperative variables, all PROs recorded in this study were similar between the 2 payer groups at baseline and 12 weeks postoperatively (P > .05). Furthermore, ΔPRO scores from baseline to 12 weeks were also similar (P > .05). CONCLUSIONS: After adjusting for patient-specific variables, PROs are similar at baseline and 12 weeks postoperatively between commercial and Medicare cohorts. For TKA candidates with similar baseline demographics, surgeons can expect similar perioperative PROs regardless of insurance type.